Aporetics Community: Tensions Between Policy and the Political (Andamios, Revista de Investigación Social, 2014)
We analyze the status of the community from the perspective of Post-Foundational Thought. This approach allows us to reflect about the relationship between politics and the political, which also allows us to question the need for a strong ontological foundation of the real political life. Based on some ideas of Martin Heidegger, the Being is no longer a foundation but now is conceived as an Event. In this way, is possible to think this foundation as something hidden and removed.  From these ideas is then possible to consider the community in nonessentialist terms, as a contradictory reality that is only feasible if it is not feasible.
Keywords: Community; Paradox; the Political; Politics; Post-Foundational Thought